Rainfall-triggered debris flows: triggering-propagation modelling and application to an event in Southern Italy. Issue 1 (August 2021) - Porta, G La; Leonardi, A; Pirulli, M; Castelli, F; Lentini, V
Abstract: Debris flows are high-speed and unpredictable phenomena, considered among the main sources of hazard worldwide, since they can affect structures, the economy, and human lives. Rainfall typically triggers these events, causing the flowing of the unconsolidated soil downslope. This work focuses on debris-flow events characterized by multiple triggering areas, which are extremely complex since they involve a spatial sequence of numerous triggers in a relatively small portion of the slope. Numerical modelling of this type of phenomenon can contribute to hazard and risk assessment, which is key to designing effective mitigation structures. In this article, two different models are applied for triggering and propagation, respectively. The former computes the transient pore-pressure changes and the consequent factor of safety variation caused by rainfall infiltration, inducing the triggering of the event. The latter is a depth-averaged numerical model that simulates the event runout, and whose parameters are calibrated through back-analysis. The applicability of the two combined approaches is tested through modelling of an historical event in Southern Italy, which was characterized by large mass releases from multiple triggering zones. Residential areas were hit, suffering serious consequences. Two rheologies are compared to individuate the most suitable propagation model for the study case and obtained results are commented.